Impaired cognitive flexibility following NMDAR-GluN2B deletion is associated with altered orbitofrontal-striatal function. (1st November 2021) - Marquardt, Kristin; Josey, Megan; Kenton, Johnny A.; Cavanagh, James F.; Holmes, Andrew; Brigman, Jonathan L.
Highlights: Neuronal firing rates are altered by corticohippocampal GluN2B deletion, both in the cortex and dorsal striatum. GluN2B deletion disrupts communication between the orbital frontal cortex and dorsal striatum driving the continuation of unrewarded responses. Our data demonstrate corticostriatal coordination is necessary for optimal behavioral flexibility. These results suggest GluN2B containing NMDARs are a key molecular component in mediating neuronal timing. Abstract: A common feature across neuropsychiatric disorders is inability to discontinue an action or thought once it has become detrimental. Reversal learning, a hallmark of executive control, requires plasticity within cortical, striatal and limbic circuits and is highly sensitive to disruption of N -methyl-d -aspartate receptor (NMDAR) function. In particular, selective deletion or antagonism of GluN2B containing NMDARs in cortical regions including the orbitofrontal cortex (OFC), promotes maladaptive perseveration. It remains unknown whether GluN2B functions to maintain local cortical activity necessary for reversal learning, or if it exerts a broader influence on the integration of neural activity across cortical and subcortical systems. To address this question, we utilized in vivo electrophysiology to record neuronal activity and local field potentials (LFP) in the orbitofrontal cortex and dorsal striatum (dS) of mice with deletion of GluN2B in neocortical and hippocampal principal cells while they performed touchscreen reversal learning. Reversal impairment produced by corticohippocampal GluN2B deletion was paralleled by an aberrant increase in functional connectivity between the OFC and dS. These alterations in coordination were associated with alterations in local OFC and dS firing activity. These data demonstrate highly dynamic patterns of cortical and striatal activity concomitant with reversal learning, and reveal GluN2B as a molecular mechanism underpinning the timing of these processes.